Construction of dual nanomedicines for the imaging and alleviation of atherosclerosis - Shuihua Zhang; Wan Xu; Peng Gao; Wenli Chen; Quan Zhou (Artificial Cells, Nanomedicine, and Biotechnology, 2020)
Magnetic resonance imaging (MRI) is an essential tool for the diagnosis of atherosclerosis, a chronic cardiovascular disease. MRI primarily uses superparamagnetic iron oxide (SPIO) as a contrast agent. However, SPIO integrated with therapeutic drugs has rarely been studied. In this study, we explored biocompatible paramagnetic iron-oxide nanoparticles (NPs) in a complex with low pH-sensitive cyclodextrin for the diagnostic imaging and treatment of atherosclerosis. The NPs were conjugated with profilin-1 antibody (PFN1) to specifically target vascular smooth muscle cells (VSMCs) in the atherosclerotic plaque and integrated with the anti-inflammatory drug, rapamycin. The PFN1-CD-MNPs were easily binded to the VSMCs, indicating their good biocompatibility and low renal toxicity over the long term. Ex vivo near-infrared fluorescence (NIRF) imaging and in vivo MRI indicated the accumulation of PFN1-CD-MNPs in the atherosclerotic plaque. The RAP@PFN1-CD-MNPs alleviated the progression of arteriosclerosis. Thus, PFN1-CD-MNPs served not only as multifunctional imaging probes but also as nanovehicles for the treatment of atherosclerosis.